Models of Multicultural Education in Efforts to Grow Tolerance in the Guidance Center of SMP An Nahdloh Malaysia - Firdaus, Rizki Anugrah; Sunarto, Sunarto; Cahyono, Hadi; Asmaroini, Ambiro Puji; Umam, Muhammad Khairul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The research aims: 1. To introduce the multicultural education model to students through the hierarchical learning media of the Pancasila pyramid. 2. To find out the activities in the Guidance Studio of An Nahdloh Malaysia which have tolerance values. 3. To increase tolerance between students at the An Nahdloh Malaysia Guidance Studio. This research method uses a qualitative approach, collecting data through observation, interviews, and documentation. From the results of observations in the field through observations at the An Nahdloh Middle School Guidance Studio, the majority of students do not have official or illegal citizenship documents. They do not have official citizenship documents because they follow their parents, who come from Indonesia and work in Malaysia as Indonesian migrant workers. And there are still students who discriminate by making fun of their friends. Apart from that, some student's friends are ostracized. Activities carried out by teachers are by providing material about tawasuh (moderate), tawazun (standing), i'tidal (fair), and tasamuh (tolerant). Then, students' activities to maintain harmony by carrying out daily activities at the cottage, such as eating, playing futsal, praying, and cleaning the cottage. From the activities carried out by the school principal and researchers, it can be concluded that all of them have values that build tolerance attitudes and increase insight into multiculturalism. It is hoped that this can foster an attitude of tolerance and strengthen relationships between students in dealing with cultural differences in the studio. Guidance from An–Nahdloh Malaysia